Modulation of NMDA and AMPA/kainate receptors by tocotrienol-rich fraction and α-tocopherol in glutamate- induced injury of primary astrocytes - Abedi, Zahra (2017)
Neurodegenerative diseases such as Huntington's, Alzheimer's, Parkinson's disease and stroke are the most common diseases suffered by the aged population. Glutamate is considered as a main excitatory amino acid neurotransmitter in the mammalian central nervous system which can be excitotoxic, playing a key role in series of chronic neurodegenerative diseases. The Vitamin E which consist of tocopherol and tocotrienols, are different in their side chain either in saturated or unsaturated phytyl tail. Previous studies have demonstrated that tocopherol and tocotrienol have protective effects against glutamate toxicity in an astrocytic cell line. The aim of current study is to demonstrate the potential of tocopherol and tocotrienol in protecting glutamate injured primary astrocytes. For this purpose, the primary astrocytes were isolated from mixed glial cells of C57BL/6 mice by using the Easysep Mouse CD11b positive selection kit and cultured in supplemented DMEM. Mixed glial cultures were treated with 50-75 mM L-leucine methyl ester (LME) for 60-90 minutes to improve purity of cultures. The purity of primary astrocytes was measured by flow-cytometer and is approximately 79.4%. The IC20 and IC50 values of glutamate were determined by MTT assay at 10 mM and 100 mM respectively. Cell were induced injury at IC20 and IC50 of glutamate and the effects of tocopherol and tocotrienol rich fraction (TRF) was determined.in pre and post-treatment study. For the high yield of RNA, the IC20 of glutamate was used in the experiment. Exposure to 100 mM of glutamate in primary astrocytes reduced cell viability by approximately 64.75 % and 61.10 % in pre and post treatment study respectively. The mitochondrial membrane potential (MMP) detected in primary astrocytes were assessed with 100, 200 and 300 ng/ml concentration of TRF and α-Tocopherol. The results depicted that pre-treatment with TRF and α-Tocopherol caused the mitochondrial activity to achieve 88.46%, 82.42%, 80.74% and 93.31%, 87.51%, 83.70%, respectively. In post-treatment study, with increase of TRF (100, 200 and 300 ng/ml) concentration causes the increase to 61.21%, 73.01%, 78.43% of MMP value. Similarly, increase of MMP value from 66.12%, 76.46%, and 81.22% was observed with increasing concentration of α-Tocopherol. Then the expression of ionotropic glutamate receptors genes was elucidated using Real-time PCR. The gene of interest consists of the Gria2 (Glutamate Receptor, Inotoropic AMPA), GRIK1 (Glutamate Receptor, Ionotropic, kainate1) and Grin2A (Glutamate Receptor, Ionotropic, N-Methyl D-Aspartate 2A). The results showed that in both pre and post studies, the ionotropic glutamate receptors genes were down regulated after the treatment and α- tocopherol played an important role in down regulating the genes. The most affected genes were Gria2, GriK1 and Grin2A respectively in both pre and post studies. Decreased intracellular calcium concentration also was observed indicating the present of vitamin E altered the polarization of astrocytes. As a conclusion, this study shown that α- tocopherol is more effective and only required low concentration of α- tocopherol for prophylactic purposes compared to post-treatment in primary astrocytes cells.